PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH KABUPATEN SUKOHARJO - Makruf, Imam (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
This study aimed to analyze various ICT-based media and learning resources used in learning Arabic, the selection or development process, the process of using it in learning, and the learning outcomes. Research data collected from observations, documentation, and interviews were validated with FGD and analyzed with interactive models. The results of this study show that; (1) the most widely used media in learning Arabic is powerpoint presentations with LCD and language laboratories, then video, audio and games, (2) the process of selecting developing media and learning resources is done by design and by utilization, (3) the process of utilizing media and learning resources is done more for the delivery of material at the core activities in addition to enrichment and assignment, and (4) media and learning resources for Arabic-based ICT that use material from native speakers have a positive impact on improving the motivation, self confidence, and Arabic competence of students.